1978
DOI: 10.1002/ijc.2910220608
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalites in evening plasma prolactin levels in nulliparous women with benign or malignant breast disease

Abstract: In the present study the assay results of prolactin concentrations in serial samples of blood obtained from premenopausal women with benign or malignant disease of the breast are compared with--and discussed in relation to--findings reported in earlier studies based on single samples of blood taken at various times from a large and ostensibly normal population of women. The finding of an abnormality in nycthemeral prolactin levels in the established disease is considered to strengthen the concept that the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The authors of that study interpreted these findings to be an indication of "persistent estrogenic stimulation" among women with BBD, though it is obvious that the benign conditions considered together in their report were quite heterogeneous. Tarquini et al (59) reported abnormally high plasma prolactin levels in premenopausal nulliparous women with both benign (dysplasia and fibroadenoma) and malignant disease compared to a large series of presumably healthy women, but the findings were not confirmed among parous women who had benign disease and numbers in the study are small. Grattarola (60) measured testosterone and androstanediol levels in 26 women with fibrocystic disease and 18 normal women of the same age range; he found significantly higher mean values for both hormones in the benign disease group.…”
Section: Endogenous Hormone Levelsmentioning
confidence: 84%
“…The authors of that study interpreted these findings to be an indication of "persistent estrogenic stimulation" among women with BBD, though it is obvious that the benign conditions considered together in their report were quite heterogeneous. Tarquini et al (59) reported abnormally high plasma prolactin levels in premenopausal nulliparous women with both benign (dysplasia and fibroadenoma) and malignant disease compared to a large series of presumably healthy women, but the findings were not confirmed among parous women who had benign disease and numbers in the study are small. Grattarola (60) measured testosterone and androstanediol levels in 26 women with fibrocystic disease and 18 normal women of the same age range; he found significantly higher mean values for both hormones in the benign disease group.…”
Section: Endogenous Hormone Levelsmentioning
confidence: 84%
“…Kwa and his colleagues [187] reported a peak of prolactin in the early evening in nulliparous women with BBD, which did not occur in parous women. Walsh and his colleagues [198] found that nulliparous women with mastodynia had elevated evening levels compared to parous women.…”
Section: (B) Prolactinmentioning
confidence: 96%
“…In post-menopausal women who developed breast cancer, the prolactin levels were significantly elevated, being at or above the 70th percentile for the controls. In this group the results are consistent with prolactin acting as a late-stage tumour promoter.There is no doubt that prolactin is an important factor in the induction and maintenance of mammary carcinoma in the rat and mouse (Pearson et al, 1969;Wang and Bulbrook, 1977;Boot, 1970) but its role in man is equivocal (Bulbrook and Wang, 1979;Nagasawa, 1978). Evidence that the hormone may be a determinant of risk of breast cancer comes from the findings of raised levels of plasma prolactin in women with a family history of the disease (Kwa et al, 1976 , 1972).…”
mentioning
confidence: 93%
“…There is no doubt that prolactin is an important factor in the induction and maintenance of mammary carcinoma in the rat and mouse (Pearson et al, 1969;Wang and Bulbrook, 1977;Boot, 1970) but its role in man is equivocal (Bulbrook and Wang, 1979;Nagasawa, 1978). Evidence that the hormone may be a determinant of risk of breast cancer comes from the findings of raised levels of plasma prolactin in women with a family history of the disease (Kwa et al, 1976, in nulliparous obese postmenopausal women (Kwa et al, 1978) in women with benign breast disease (Tarquini et al, 1978) and in some, but not all, case-control studies (Boyns et al, 1973;Franks et al, 1974;Cole et al, 1977;Herman et al, 1981;Murray et al, 1972).…”
mentioning
confidence: 99%